The informal seed business: Focus on yellow bean in Tanzania - Sperling, Louise; Birachi, Eliud Abucheli; Kalemera, Sylvia Monica; Mutua, Mercy Muli; Templer, Noel Anyuka; Mukankusi, Clare; Radegunda, Kessy Francis; Williams, Magdalena; Gallagher, Patrick; Kadege, Edith; Rubyogo, Jean-Claude (MDPI, 2021)
This article explores the informal seed business, focusing on the yellow bean in Tanzania. The yellow bean is a major bean type traded, yet little is known about the seed supply that fuels it. The survey research in 2019 encompassed larger grain traders, informal seed traders, and retailers, covered major production, distribution and sale hubs, and was complemented by GIS mapping of seed and grain flows and DNA fingerprinting of yellow bean samples. Results showed that traders buy and sell grain and informal seed: it is not one business or the other, but both. Informal seed is an important moneymaker, representing between 15 and 40% of trader business in non-sowing and sowing periods, respectively. In the year monitored, 100% of the yellow bean seed was drawn from the informal sector, amounting to $US 4.35 million just among those sampled. Nevertheless, the informal and formal sectors are clearly linked, as over 60% of the beans sampled derived from modern varieties. Informal traders prove key for: sustaining the grain business, serving the core of the seed business, and moving varieties at scale. More explicit efforts are needed to link the informal sector to formal research and development partners in order to achieve even broader impacts.